Optimalisasi Kinerja Bank Nagari Cabang Sawahlunto dalam Mendukung Pembangunan Ekonomi Daerah melalui Pendekatan Strategis Berbasis Analisis SWOT - Ade Rahmat Ihsan; Syafwandi (PT. Hasba Edukasi Mandiri, 2025)
This study aims to formulate strategies to optimize the performance of Bank Nagari's Sawahlunto Branch in supporting regional economic development through a SWOT analysis approach. As a Regionally-Owned Enterprise (BUMD), Bank Nagari plays a dual role as a financial institution and development agent through dividend contributions, Corporate Social Responsibility (CSR) programs, and support for the MSME sector and local cultural preservation. The research method uses a descriptive-analytical qualitative approach with data collection techniques through in-depth interviews, documentation studies, and participatory observation. The analysis results identify key strengths in strategic synergy with the Sawahlunto City Government and commitment to local culture, while weaknesses lie in geographical reach limitations and digital product diversification. Opportunities arise from the tourism sector development and financial technology adoption, while threats come from competition with fintech and natural disaster vulnerabilities. Based on the SWOT matrix, four main integrated strategies are formulated to strengthen the bank's contribution to regional economic development.